2021
DOI: 10.1007/s10934-021-01102-3
|View full text |Cite
|
Sign up to set email alerts
|

New CeO2–TiO2, WO3–TiO2 and WO3–CeO2–TiO2 mesoporous aerogel catalysts for the low temperature selective catalytic reduction of NO by NH3

Abstract: New mesoporous and well-structured aerogel catalysts (CeO 2 -TiO 2 , WO 3 -TiO 2 and WO 3 -CeO 2 -TiO 2 ) were elaborated via the sol gel method, characterized by means of various techniques (XRD; N 2 -Physisorption at 77 K; NH 3 -TPD; H 2 -TPR; DRUV-Vis spectroscopy) and evaluated in the selective catalytic reduction (SCR) of NO by NH 3 . The results reveal that all the aerogel catalysts develop essentially the diffraction peaks of TiO 2 anatase phase and are classified as mesoporous materials with a high sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Yu et al [29], investigated a series of sulfated catalysts (CuSO 4 /TiO 2 , Fe 2 (SO 4 ) 3 /TiO 2 , MnSO 4 /TiO 2 , Ce(SO 4 ) 2 /TiO 2 and CoSO 4 /TiO 2 ) in the NH 3 -SCR reaction and demonstrated that the amount of acid sites was the main factor which affects the catalytic activity of metal sulfate catalysts. Furthermore, in our previous work [26], we showed that WO 3 -CeO 2 -TiO 2 exhibits higher SCR activity than WO 3 -TiO 2 and CeO 2 -TiO 2 aerogel catalysts due to the synergetic effect between W and Ce which influences the acidity and reducibility of catalyst. Li et al [30] reported that a novel CeO 2 /TiO 2 -MoO 3 catalyst exhibits100% NO conversion at 200-350 °C.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Yu et al [29], investigated a series of sulfated catalysts (CuSO 4 /TiO 2 , Fe 2 (SO 4 ) 3 /TiO 2 , MnSO 4 /TiO 2 , Ce(SO 4 ) 2 /TiO 2 and CoSO 4 /TiO 2 ) in the NH 3 -SCR reaction and demonstrated that the amount of acid sites was the main factor which affects the catalytic activity of metal sulfate catalysts. Furthermore, in our previous work [26], we showed that WO 3 -CeO 2 -TiO 2 exhibits higher SCR activity than WO 3 -TiO 2 and CeO 2 -TiO 2 aerogel catalysts due to the synergetic effect between W and Ce which influences the acidity and reducibility of catalyst. Li et al [30] reported that a novel CeO 2 /TiO 2 -MoO 3 catalyst exhibits100% NO conversion at 200-350 °C.…”
Section: Introductionmentioning
confidence: 87%
“…The powder aerogels (TiO 2 , CeO 2 -TiO 2, CeO 2 -TiO 2 -SO 4 2and WO 3 -CeO 2 -TiO 2 ) were prepared via the one step sol gel protocol, then dried under the supercritical drying conditions of solvent (ethanol). The detailed method adopted for the elaboration of samples was described in our previous works [20,26]. Ammonium metatungstate hydrate ((NH 4 ) 6 H 2 W 12 O 24 .xH 2 O, Sigma Aldrich, > 99.9%) and cerium nitrate (Ce(NO 3 ) 3 .6H 2 O, Aldrich) were used as W and Ce precursors, respectively.…”
Section: Synthesis Of Ce Based Nanoporous Aerogel Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al [29] studied the effect of CeO 2 modification on the low-temperature NH 3 -SCR activity of the V 2 O 5 -WO 3 /TiO 2 catalyst. They demonstrated that V-O-Ce bridging bonds were formed in the catalyst, and the reducibility of the catalyst was enhanced due to the synergistic effect between Ce and V. The introduction of WO 3 can improve the NH 3 -SCR activity of the catalyst by increasing the redox property and Brönsted acidity [30]. Indeed, Lietti et al [31] observed that the V 2 O 5 -WO 3 /TiO 2 catalyst has both higher transient and steady-state reactivity in SCR than the binary V 2 O 5 /TiO 2 counterpart.…”
Section: Introductionmentioning
confidence: 99%